Factors and expectations influencing concussion disclosure within NCAA Division I athletes: A mixed methodological approach - Melissa C. Kay; Heidi Hennink-Kaminski; Zachary Y. Kerr; Paula Gildner; Brittany M. Ingram; Kenneth L. Cameron; Megan N. Houston; Laura A. Linnan; Stephen W. Marshall; Karen Y. Peck; Johna K. Register-Mihalik (Elsevier, 2023)
Background: Participation in sports is associated with many benefits to all aspects of health; however, it also comes with the risk of injury, particularly concussions. Self-disclosure and care seeking following a concussion are especially important because of the lack of outwardly visible signs and/or symptoms. Although recent research has explored factors affecting concussion disclosure, use of isolated methodologies limits the ability to contextualize how disclosure or nondisclosure occurs. Therefore, the purpose of this study was to describe the factors and expectations of National Collegiate Athletic Association (NCAA) athletes that may influence concussion disclosure. Methods: This mixed-methods convergent parallel research study included 25 NCAA Division I athletes representing 13 sports, all of whom completed a concussion-education session with pre-/post-test surveys and a semistructured interview. Eligible athletes were at least 18 years old and on an NCAA roster. The surveys focused on previous concussion-related disclosure behaviors, knowledge, attitudes, beliefs, norms, and intentions about disclosing concussion. Interviews focused on the athletes' experiences related to concussion disclosure. Survey data were analyzed using descriptive statistics and Mann-Whitney U tests. Interviews were analyzed using a Consensual Qualitative Research tradition. Results: Participants had good concussion knowledge (median = 46.0), positive attitudes (median = 38.0), strong beliefs (median = 13.0), and strong intentions to disclose concussion symptoms (median = 7.0). None of the constructs differed by participants' gender. Although quantitative findings were mostly positive, interview data highlighted factors that may explain why some participants are successful in disclosing concussions and why others may find disclosure difficult. Educational efforts, sport culture, and medical professional presence were the primary facilitators discussed by participants. Stigma, pressure, and a lack of team support were perceived as disclosure barriers. Conclusion: The context in which concussion disclosure occurs or does not occur is vital to the success of educational interventions. Interventions must prioritize stakeholder- and team-based perspectives on concussion to establish a network supportive to disclosure.